Emergent Supersymmetry at the Ising-Berezinskii-Kosterlitz-Thouless Multicritical Point - Huijse, Liza; Bauer, Bela; Berg, Erez (Physical review letters, 2015)
We show that supersymmetry emerges in a large class of models in 1 + 1 dimensions with both Z2 and U(1) symmetry at the multicritical point where the Ising and Berezinskii-Kosterlitz-Thouless transitions coincide. To arrive at this result we perform a detailed renormalization group analysis of the multicritical theory including all perturbations allowed by symmetry. This analysis reveals an intricate flow with a marginally irrelevant direction that preserves part of the supersymmetry of the fixed point. The slow flow along this special line has significant consequences on the physics of the multicritical point. In particular, we show that the scaling of the U(1) gap away from the multicritical point is different from the usual Berezinskii-Kosterlitz-Thouless exponential gap scaling.